Development and Feasibility Test on Android-Based Interactive Multimedia Applications for Mathematics Learning - Ganda Yoga Swara; Muhammad Giatman; Ambiyar Ambiyar; Wakhinuddin Simatupang; Nizwardi Jalinus; Rijal Abdullah (Universitas Negeri Padang, 2021)
This study aims to produce and test the feasibility of interactive multimedia application products for learning mathematics for elementary schools. This research was conducted at SD Negeri 07 Padang City using the Research and Development method of the APPED development model. In the process, the APPED development model consists of 5 steps, namely the analysis and initial research, Design, Production, Evaluation and Dissemination stages. The results of this study indicate that the resulting interactive multimedia application product is suitable for use by elementary students. The conclusion of this study is that this interactive multimedia application can create an effective and integrated online learning process between teachers and students. Make it easier for elementary students to learn mathematics anywhere and anytime. This interactive multimedia product is feasible as a learning medium based on the results of trials and evaluations of media or application experts and teachers with a score of 3.85 (high).